PERANCANGAN KONSTRUKSI SLOPEWAY SEBAGAI JEMBATAN PENGHUBUNG ANTARA GELADAK NO. 1A DENGAN GELADAK NO. 1B PADA KM. DHARMA RUCITRA VIII MILIK PT. DHARMA LAUTAN UTAMA - Ali Reza Muthahhari; IR. Hariyanto Soeroso, M.T.; Dhika Aditya Purnomo, S.ST., M.T. (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
In this study, designing a slopeway construction that serves as a connecting bridge between No. 1A Deck with No. 1B Deck on KM. Dharma Rucitra VIII so that it can be used as access to unload and load motorbikes. The stages of the slopeway construction design process will follow the applicable standards of the Biro Klasifikasi Indonesia (BKI). Thestages of the slopeway construction design process begin by calculating the cross-sectional modulus of the planned slopeway construction. Comparing the results of the calculation of the cross-sectional modulus of slopeway construction with the requirements of the crosssectional modulus that have been determined by BKI. Furthermore, carrying out the loading simulation process will use the FEM (fenite element methods) approach using the ANSYS Workbench software. Comparing the simulation results of slopeway construction loading with the allowable stresses determined by BKI. The results of this study indicate that design 3 has better quality than designs 1 and 2. The size of the construction is 8 mm thick plate, main web beam T 250x100x10, side and center girder T 250x120x10, supporting web beam L75x75x6, long girder L75x75x6. The equivalent stress value is 122.16 MPa, the bending stress is 75,458 MPa, the shear stress is 70,452 MPa, the strain is 6.30E04, the deformationis 5,1674 mm and has a construction weight of 5099.8 kg with a total budget of Rp. 18,159,579.27.